Academic forensic psychiatry - Taylor, Pamela J. (Seminars in forensic psychiatry, 2024)
Forensic psychiatry, of all the specialties in medicine, needs its own strong academic core. Academic forensic psychiatry is founded in scientific research, with its systematic approach to making and recording observations, formulating hypotheses from them, testing those hypotheses with new observations and accumulating the most comprehensive picture possible in a way that is transparent and replicable. An academic approach supports application of scientific principles as strongly in the individual case as in developing relevant collective knowledge, is able to make links between them and can communicate all this effectively within and outside the specialty. This requires highly developed and defined specialist training. Academic forensic psychiatry in this sense is the business of all forensic psychiatrists. In order for forensic psychiatry to thrive, however, it is vital that some forensic psychiatrists further specialise in academic work in terms of additional training, time and immersion in skills that support accurate scientific questioning and testing and, ultimately, the capacity to innovate and keep this cycle active.